MicroRNA miR‐204 regulates proliferation and differentiation of oligodendroglia in culture. Issue 10 (16th March 2020) - Wittstatt, Jan; Weider, Matthias; Wegner, Michael; Reiprich, Simone
Abstract: Oligodendrocytes wrap and physically shield axons of the central nervous system with myelin sheaths, resulting in rapid signal transduction and accurate neuronal function. The complex oligodendroglial development from immature oligodendrocyte precursor cells (OPCs) to myelinating oligodendrocytes (OLs) is profoundly dependent on the activity of transcription factors of the Sox protein family. Target genes of the crucial regulator Sox10 have recently been expanded to microRNAs. Here, we report miR‐204 as a novel transcriptional target of Sox10. Regulatory regions of miR‐204 show responsiveness to and binding of Sox10 in reporter gene assays and electromobility shift assays. Once expressed, miR‐204 inhibits OPC proliferation and facilitates differentiation into OLs in the presence of Sox10 as evident from overexpression in primary rat and mouse oligodendroglial cultures. Phenotypes are at least in part caused by miR‐204‐dependent repression of the pro‐proliferative Ccnd2 and the differentiation inhibiting Sox4. These findings argue that the transcriptional activator Sox10 forces oligodendroglial cells to exit the cell cycle and start differentiation by gene inhibition via miR‐204 induction. Abstract : Sox10 induces miR‐204 expression in oligodendroglial cells. miR‐204 reduces proliferation and increases differentiation of primary oligodendroglia. miR‐204 functions at least in part by inhibiting Cyclin D2 and Sox4.